Successful manual reduction for ureterosciatic hernia: A case report. (2019) - Kimura, Jiro; Yoshikawa, Kentaro; Sakamoto, Takashi; Lefor, Alan Kawarai; Kubota, Tadao
Highlights: Manual reduction was successfully performed for a patient with sciatic hernia. There were no report of closed manual reduction previously. A sciatic hernia in women may be manually reduced without surgery. Abstract: Introduction: Sciatic hernias are the least common type of pelvic floor hernias. The purpose of this study was to present a novel technique for manual reduction and to conduct a systematic review of previous reports of sciatic hernias to characterize them and review the outcomes. Presentation of case: An 86-year-old female presented with left-sided lumbar pain. She had a past medical history of rheumatoid arthritis and was treated with prednisolone and methotrexate. Her left abdomen and left lumbar area were tender. An unenhanced abdominal computed tomography scan revealed invagination of the left ureter into the left sciatic foramen and a dilated left proximal ureter and renal pelvis. Ultrasonography showed an invaginated left ureter viewing from the left buttock. She was diagnosed with a sciatic hernia. Ultrasound-guided manual transvaginal reduction was performed. Post-procedure unenhanced abdominal computed tomography scan confirmed reduction of the ureter. After 10-months of follow-up, there is no evidence of recurrence. Discussion: Previous reports of patients with sciatic hernia were identified. Clinical data associated with the hernia, reduction technique and clinical outcomes were collected for 72 patients. Open reduction was performed in 24 patients. A ureteral stent was placed in eight patients when the hernia contained the ureter. Four postoperative complications including one death were reported in adults. There were no reports of closed manual reduction. Conclusion: A sciatic hernia in women may be manually reduced without surgery. Further reviews of this rare entity are needed to determine the best management strategy.